2013
DOI: 10.1002/micr.22190
|View full text |Cite
|
Sign up to set email alerts
|

Heparin‐induced thrombocytopenia and thrombosis as an under‐diagnosed cause of flap failure in heparin‐naive patients: A case report and systematic review of the literature

Abstract: Due to the rapid and unpredictable onset of HITT during microsurgery, we recommend maintaining an index of suspicion for HITT in flaps with otherwise unexplained early thrombosis. We also encourage hematology consultation, discontinuing heparin use and initiating alternate thromboprophylaxis in order to inhibit the potential for subsequent life-threatening systemic complications as well as improving the potential for delayed reconstructive success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 28 publications
(39 reference statements)
0
30
0
Order By: Relevance
“…It is only at a later stage that the probability of heparininduced thrombocytopenia syndrome [7][8][9][10][11][12][13] was revealed, as a possible major contributor to the four consecutive flap failures we observed.…”
Section: Discussionmentioning
confidence: 63%
“…It is only at a later stage that the probability of heparininduced thrombocytopenia syndrome [7][8][9][10][11][12][13] was revealed, as a possible major contributor to the four consecutive flap failures we observed.…”
Section: Discussionmentioning
confidence: 63%
“…Tessler et al 11 in their review in 2013 analysed the literature by dividing papers in 3 groups: prior heparin exposure, heparin naive and prior heparin status not discussed. In each group, the number of patients, HITT flap characteristics, time until flap failure, treatment of HITT and confirmation of HITT by antibody test were analysed.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports of failed flap reconstruction attributed to HIT exist in the literature (Table 1) (2,(6)(7)(8). In cases reported by Schleich et (7) and Tremblay et al (6), the venous thrombotic events occurred intraoperatively and postoperatively.…”
Section: Discussionmentioning
confidence: 98%
“…In recent years, studies have shown that patients with normal or even high platelet counts may also develop HIT (1,5). Among patients with flap failure secondary to HIT, thrombocytopenia was the presenting feature of HIT in <50% (Table 1) (2,(6)(7)(8). This raises a significant concern regarding the applicability of the 4T scoring system (a pretest probability assessment of HIT) in our patient population, because three of four criteria are related to thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation